Nyt fra religionspsykologien - Nørager, Troels (Religionsvidenskabeligt Tidsskrift, 1991)
This article is a review of the two recent and highly significant contributions to the existing literature on the psychology of religion. The International Journal for the Psychology of Religion is criticized for its tendency to restrict the field to psychological approaches that can be tested empirically. In marked contrast to this, David Wulff’s comprehensive landmark presentation of what might - William James in memoriam - aptly be called "The arieties of the Psychology of Religion", sees the diversity of opinions and approaches as a positive (and in any event inevitable) result of the influence of "the personal factor". No doubt, Wulff’s Psychology of Religion: Classic and Contemporary Views will for decades stand out as the introduction to a complex, highly problematic but at the same time fascinating field of research.